2008
DOI: 10.1038/cdd.2008.159
|View full text |Cite
|
Sign up to set email alerts
|

Prothymosin-α plays a defensive role in retinal ischemia through necrosis and apoptosis inhibition

Abstract: Prothymosin-a (ProTa) causes a switch in cell death mode from necrosis to neurotrophin-reversible apoptosis in primary cultured cortical neurons. In the present study, post-ischemic administration (3 or 24 h, intravenously) of recombinant mouse ProTa without neurotrophins completely prevented ischemia-induced retinal damage accompanying necrosis and apoptosis, as well as dysfunction assessed by electroretinogram. Treatments with anti-erythropoietin (EPO) or brain-derived neurotrophic factor (BDNF) immunoglobul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
90
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(99 citation statements)
references
References 33 publications
6
90
0
Order By: Relevance
“…the retinal ischemia model, the ischemic stress depletes ProTa from the retinal cells, and the intravitreous pretreatments with anti-ProTa IgG or antisense oligodeoxynucleotide against ProTa deteriorated the ischemic damage. 7 Therefore, it is evident that ProTa is extracellularly released from nuclei on ischemic stress, and that it exerts endogenous neuroprotective functions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…the retinal ischemia model, the ischemic stress depletes ProTa from the retinal cells, and the intravitreous pretreatments with anti-ProTa IgG or antisense oligodeoxynucleotide against ProTa deteriorated the ischemic damage. 7 Therefore, it is evident that ProTa is extracellularly released from nuclei on ischemic stress, and that it exerts endogenous neuroprotective functions.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this speculation was confirmed by in vivo study, in which exogenous ProTa inhibited both necrosis and apoptosis of retinal cells after ischemia, but the further treatment with anti-BDNF antibody disclosed the apoptosis induction by ProTa. 7 It should be noted that ProTa in the cytosol inhibits apoptosis through an inhibition of apoptosome formation in non-neuronal HeLa cells. 4 Furthermore, there is a report that ProTa is released from the nuclei when the NLS is cleaved off by caspase-3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous in vitro studies have shown that ProT␣ is capable of preventing apoptotic cell death by inhibiting the formation of the apoptosome, a large cytosolic macromolecular complex formed in cells committed to programmed death (10). Recent in vivo studies have also revealed that ProT␣ not only inhibits apoptotic cell death but also suppresses necrotic cell death following ischemic stroke (17,18). In this report, using cell culture models of HD, we demonstrate that ProT␣ interacts with mHtt and reduces mHtt-caused cytotoxicity.…”
mentioning
confidence: 69%
“…Because necrotic cell death is an overwhelming pathway by which cells die under specific cell culture condition, the overall effect of ProT␣ should still be protective (18). In ischemic stroke mouse studies, administration of purified ProT␣ remarkably inhibited both necrotic and apoptotic cell death (18).…”
Section: Discussionmentioning
confidence: 99%